Insights into the function of HDAC3 and NCoR1/NCoR2 co-repressor complex in metabolic diseases - Paluvai, Harikrishnareddy; Doddi, Shanmukha K.; Tyedmers, Jens; Backs, Johannes (Frontiers in molecular biosciences, 2023)
Histone deacetylase 3 (HDAC3) and nuclear receptor co-repressor (NCoR1/2) are epigenetic regulators that play a key role in gene expression and metabolism. HDAC3 is a class I histone deacetylase that functions as a transcriptional co-repressor, modulating gene expression by removing acetyl groups from histones and non-histone proteins. NCoR1, on the other hand, is a transcriptional co-repressor that interacts with nuclear hormone receptors, including peroxisome proliferator-activated receptor gamma (PPARγ) and liver X receptor (LXR), to regulate metabolic gene expression. Recent research has revealed a functional link between HDAC3 and NCoR1 in the regulation of metabolic gene expression. Genetic deletion of HDAC3 in mouse models has been shown to improve glucose intolerance and insulin sensitivity in the liver, skeletal muscle, and adipose tissue. Similarly, genetic deletion of NCoR1 has improved insulin resistance and reduced adiposity in mouse models. Dysregulation of this interaction has been associated with the development of cardio-metabolic diseases such as cardiovascular diseases, obesity and type 2 diabetes, suggesting that targeting this pathway may hold promise for the development of novel therapeutic interventions. In this review, we summarize the current understanding of individual functions of HDAC3 and NCoR1/2 and the co-repressor complex formation (HDAC3/NCoR1/2) in different metabolic tissues. Further studies are needed to thoroughly understand the mechanisms through which HDAC3, and NCoR1/2 govern metabolic processes and the implications for treating metabolic diseases.
Gesehen am 25.09.2023